PENGARUH BPHTB DAN PBB TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI KEPULAUAN RIAU - Yusran, Rio Rahmat; Siregar, Dian Lestari (EDUTECH CONSULTANT, 2017)
The city of Batam and Tanjung Pinang is one of the few districts / municipalities in Riau Islands Province that have population growth rates and rapid economic growth. The data used in this research is secondary data. The population of this study is the population of Riau Islands and the sampling technique using Purposive Sampling method. The method of analysis in this study using multiple linear regression analysis and hypothesis testing (T test, F test, and coefficient of determination). Data processing using Eviews 7 program assistance. The results showed that the Acquisition of Land and Building Rights (BPHTB) and Land Tax And Building (PBB) have a positive and significant impact on Riau Islands Regional Income (PAD) as evidenced by the result of f-statistic significance test of 0.000 <0,05. While partially Tax on Land and Building Acquisition (BPHTB) has a positive and significant effect on PAD with statistical significance value of 0.000 <from 0.05. Similarly, the Land and Building Tax (PBB) gives a positive and significant influence on the PAD shown by the significance of statistic t value of 0.000 <0.05.